A GPU-based Real-time Software Correlation System for the Murchison Widefield Array Prototype - Wayth, Randall; Greenhill, L.; Briggs, F. (University of Chicago Press, 2009)
Modern graphics processing units (GPUs) are inexpensive commodity hardware that offer Tflop/s theoretical computing capacity. GPUs are well suited to many compute-intensive tasks including digital signal processing. We describe the implementation and performance of a GPU-based digital correlator for radio astronomy. The correlator is implemented using the NVIDIA CUDA development environment. We evaluate three design options on two generations of NVIDIA hardware. The different designs utilize the internal registers, shared memory, and multiprocessors in different ways. We find that optimal performance is achieved with the design that minimizes global memory reads on recent generations of hardware. The GPU-based correlator outperforms a single-threaded CPU equivalent by a factor of 60 for a 32-antenna array, and runs on commodity PC hardware. The extra compute capability provided by the GPU maximizes the correlation capability of a PC while retaining the fast development time associated with using standard hardware, networking, and programming languages. In this way, a GPU-based correlation system represents a middle ground in design space between high performance, custom-built hardware, and pure CPU-based software correlation. The correlator was deployed at the Murchison Widefield Array 32-antenna prototype system where it ran in real time for extended periods. We briefly describe the data capture, streaming, and correlation system for the prototype array.